Identifying Perceptions of Health Professionals Regarding Deathbed Visions and Spiritual Care in End-of-Life Care. - Sung Ok Chang; Soo Yeon Ahn; Myung-Ok Cho; Kyung Sook Choi; Eun Suk Kong; Chun-Gill Kim; Hee Kyung Kim; Young Whee Lee; Misoon Song; Nam Cho Kim (Journal of Hospice & Palliative Nursing, 2017)
The final hours before death can be the most significant time for the dying. Adequate preparation for death can help reduce patients' fears. Research on end-of-life experiences suggests that deathbed visions are not uncommon, but many doctors and nurses find this a difficult subject to approach. A 2-round Delphi method was used to gain a reliable consensus on deathbed visions from experts in end-of-life care. A purposive sample of nurses (n = 18) and doctors (n = 13) was invited from across hospitals and nursing homes to participate in this study. In this Delphi evaluation, the health professionals' perceptions of the deathbed visions experienced by patients were identified, as well as how these phenomena should be integrated into spiritual care. The research found that healthcare professionals who are experts in end-of-life care tend to remain at the end-of-life care setting while acknowledging human spirituality as part of a peaceful death. However, they tend to not make conclusions about how death visions should be classified. This Delphi study was an attempt to identify a consensus on spiritual care including deathbed visions in end-of-life care among healthcare professionals.